Mission and Values as an Institution of a Company’s Internal Architecture - Kamosiński, Sławomir (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The aim of the research is to analyse the attitudes of entrepreneurs towards the importance of a company mission and values. Sources of inspiration for entrepreneurs were searched for in the implementation of this intangible element of the company’s internal architecture. The impact of the mission and values on the sustainability of economic organisations is discussed.Research Design & Methods: The goal was achieved on the basis of qualitative research in the form of interviews conducted among entrepreneurs from the micro, small and medium-sized enterprise sector. During the interviews, entrepreneurs were given the opportunity to speak freely. The calls were recorded in the years 2017–2019 and 2020–2021.Findings: Entrepreneurs often accept their company’s mission and values as part of its legacy. These aspects of the business are often a natural outgrowth of the process of taking over a family business from the previous generation. Some entrepreneurs consider them to be a “sentimental” factor that disturbs business, and therefore dismiss them as an unnecessary burden. Despite this, the mission and values are evident in these companies, and implemented and honored through developed rules of conduct. In the second group of companies, these intangible elements of the company’s internal architecture are implemented under the influence of external factors that result from the need to enrich the company’s marketing message.Implications / Recommendations: The results of the research lead to the conclusion that, in the light of consumer awareness of the need to respect Earth’s resources, entrepreneurs accept their company’s mission and values as an intangible element supporting the efficiency of managing today and contributing to the future.Contribution: The research supplements the disciplines of economics, finance, and management and quality science with its analysis of the intangible (cultural) factor of internal company architecture.